Pengembangan Media Pembelajaran Berbasis Adobe Animate dalam Pembelajaran IPA Kelas V Sekolah Dasar - febriyanti utami; Aren Frima; Andri Valen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aimed to develop Adobe Animate-based Learning Media for the teaching of IPA on the Human Respiratory System to Grade V A students at SD Negeri 4 Lubuklinggau. The research used a research and development model with the 4D development of Pendefinisian (Define), Perencanaan (Design), Pengembangan (Develop), and Penyebaran (Disseminate). The research was carried out on 25 students from Grade V A SD Negeri 4 Lubuklinggau. The quality of the Adobe Animate-based Learning Media developed in the research was measured using a validation questionnaire, where the quality of the learning media was found to be valid with an average score of 3.65. In terms of practicality, the Adobe Animate-based Learning Media was considered very practical with a proportion of 100%. Based on the results, it can be concluded that the development of Adobe Animate-based Learning Media in the teaching of IPA with Material on Human Respiratory System to Grade V A SD Negara 4 Lubuklinggau is valid and very practical. Keywords: Adobe Animate, Learning Media, IPA.